The Effects of SEA0400 on Ca2+ Transient Amplitude and Proarrhythmia Depend on the Na+/Ca2+ Exchanger Expression Level in Murine Models - Bögeholz, Nils; Schulte, Jan S.; Kaese, Sven; Bauer, B. Klemens; Pauls, Paul; Dechering, Dirk G.; Frommeyer, Gerrit; Goldhaber, Joshua I.; Kirchhefer, Uwe; Eckardt, Lars; Pott, Christian; Müller, Frank U. (Frontiers in Pharmacology, 2017)
Background/Objective: The cardiac Na+/Ca2+-exchanger (NCX) has been identified as a promising target to counter arrhythmia in previous studies investigating the benefit of NCX-inhibition. However, the consequences of NCX-inhibition have not been investigated in the setting of altered NCX-expression and -function, which is essential, since major cardiac diseases (heart failure/atrial fibrillation) exhibit NCX-upregulation. Thus, we here investigated the effects of the NCX-inhibitor SEA0400 on the Ca2+ transient amplitude and on proarrhythmia in homozygous-NCX-overexpressor (OE) and heterozygous-NCX-knockout (hetKO) mice compared to corresponding wild-types (WTOE/WhetKO). Methods/Results: Ca2+-transients of field-stimulated isolated ventricular cardiomyocytes were recorded with fluo-4-AM or indo-1-AM. SEA0400 (1µM) significantly reduced NCX-forward-mode function in all mouse lines. SEA0400 (1µM) significantly increased the amplitude of field-stimulated Ca2+-transients in WTOE, WThetKO and hetKO, but not in OE (% of basal; OE=98.7±5.0; WTOE=137.8±5.2*; WThetKO=126.3±6.0*; hetKO=140.6±12.8*; *p<0.05 vs basal). SEA0400 (1µM) significantly reduced the number of proarrhythmic spontaneous-Ca2+-transients (sCR) in OE, but increased it in WTOE, WThetKO and hetKO (sCR per cell; basal/+SEA0400; OE=12.5/3.7; WTOE=0.2/2.4; WThetKO=1.3/8.8; hetKO=0.2/5.5) and induced Ca2+-overload with subsequent cell death in hetKO. Conclusion: The effects of SEA0400 on Ca2+ transient amplitude and the occurrence of spontaneous Ca2+-transients as a proxy measure for inotropy and cellular proarrhythmia depend on the NCX-expression level. The antiarrhythmic effect of SEA0400 in conditions of increased NCX-expression promotes the therapeutic concept of NCX-inhibition in heart failure/atrial fibrillation. Conversely, in conditions of reduced NCX-expression, SEA0400 suppressed the NCX-function below a critical level leading to adverse Ca2+-accumulation as reflected by an increase in Ca2+ transient amplitude, proarrhythmia and cell death. Thus, the remaining NCX-function under inhibition may be a critical factor determining the inotropic and antiarrhythmic efficacy of SEA0400.